Recent trends and determinants of surge in absences among healthcare workers: The case of Padua Hospital - Daicampi, Chiara; Frasson, Enrica; Degan, Mario; Tessarin, Michele; Perina, Fabio; Stivanello, Lucia; Trevisan, Nicola; de Barbieri, Ilaria; Marcolin, Erica; Massarotto, Elena; Dotto, Federica; Zanella, Michela; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: The global shortage of healthcare professionals is critical, with the WHO reporting a deficit of 5,9 million nurses in 2020 - a number expected to increase due to rising demand and high turnover. In high-income countries, absenteeism among healthcare workers, defined as absence due to personal or health reasons, worsens this shortage, causing service disruptions, reduced productivity, and higher costs. In this context, this study examines the increase in absences among non-medical staff at the Azienda Ospedale-Università Padova (AOUP), a large hospital in the Veneto Region, employing nearly 7,000 staff.Methods: This descriptive longitudinal analysis includes all non-medical employees at AOUP, analyzing data from January 2018 to December 2023. Absence days per capita were calculated using Full-Time Equivalent (FTE) and categorized into vacation, illness, injury, maternity leave, authorized leave, unpaid leave, and COVID-related absences (from 2020 onward).Results: From 2018 to 2023, average absence days per employee rose by 2.86 days, peaking in 2022. Increases were notable in illness and injury (4.6%), authorized leave (24.8%), and unpaid leave (6.1%), while maternity leave decreased by 6.2%. Younger nurses (under 30) showed the sharpest rise in absences, while older nurses and healthcare assistants saw moderate increases. Discussion: This study is one of the first in Italy to investigate the trend in hospital staff absences. The combined impact of a surge in absences and staff shortages poses challenges for healthcare resource management. Although absence rates decreased post-pandemic, they remain above pre-pandemic levels, driven by factors like burnout and workload intensity. Between 2018 and 2023, illness and injury were leading causes of the increase in absences at AOUP, consistent with global trends. Permits, which increased by 24.8%, highlight the need to balance work with physical, mental, and family needs. Absence analysis by age revealed a significant increase among nurses under 30.